Agent-Structure Relation In Poverty Alleviation Of Fishermen: The Case Of Bangka Island, Indonesia - Nurdin, Muhamad Fadhil; Lesmana, Aditya Candra; Rachim, Hadiyanto Abdul (Department of Sociology, Faculty of Social and Political Science, Universitas Padjadjaran, 2024)
ABSTRACT This study aims to unravel the inter-relation between agent, structure, and resource system in the poverty alleviation of the fishermen community. An exploratory and descriptive approach is undertaken by involving a wide range of relevant stakeholders. The case study chosen is the fishermen community in Central Bangka District, Bangka District, and Pangkalpinang City, all located in the Province of Bangka Belitung, Indonesia This research uses a qualitative approach, with a descriptive method to gain an in-depth understanding of the research problem. The data collection process was carried out using semi-structured interviews conducted with informants, field observations, and FGDs involving various stakeholders such as the government, private sector, and fishermen group representatives. The data obtained is then validated by reducing, displaying and verifying the data. Verification refers to the rethinking process of data gathered from the field while at the same time accommodating the validation results. The results showed that the characteristics of fishermen community, added by the presence of tin mining activities has been contributing to the prolonged poverty faced by this community. The study found that government institution holds a significant role to the poverty alleviation initiatives. Three improvement strategies are proposed, covering the creation of a comprehensive regulation covering basic rights of fishermen, foster intense collaboration among sectoral institutions as well as the creation of efficient poverty alleviation policies in coastal area.Keywords: Poverty, Fishermen, Government, Collaboration Strategy, Indonesia ABSTRAK Penelitian ini bertujuan untuk mengungkap keterkaitan antara agen, struktur, dan sistem sumber daya dalam pengentasan kemiskinan masyarakat nelayan. Pendekatan eksplorasi dan deskriptif dilakukan dengan melibatkan berbagai pemangku kepentingan terkait. Studi kasus yang dipilih adalah komunitas nelayan di Kabupaten Bangka Tengah, Kabupaten Bangka, dan Kota Pangkalpinang yang semuanya berada di Provinsi Bangka Belitung, Indonesia. Penelitian ini menggunakan pendekatan kualitatif, dengan metode deskriptif untuk mendapatkan pemahaman mendalam dari permasalahan penelitian. Proses penggalian data dilakukan dengan menggunakan wawancara semi terstruktur yang dilakukan terhadap para informan, observasi lapangan, serta FGD dengan melibatkan berbagai stakeholders seperti pemerintah, swasta, perwakilan kelompok nelayan. Verifikasi mengacu pada proses berpikir ulang dari data yang dikumpulkan dari lapangan dan pada saat yang sama mengakomodasi hasil validasi. Hasil penelitian menunjukkan bahwa karakteristik masyarakat nelayan ditambah dengan adanya kegiatan penambangan timah turut berkontribusi terhadap kemiskinan berkepanjangan yang dihadapi masyarakat tersebut. Studi ini menemukan bahwa institusi pemerintah memiliki peran yang signifikan dalam upaya pengentasan kemiskinan. Tiga strategi perbaikan yang diusulkan, meliputi pembuatan regulasi yang komprehensif yang mencakup hak-hak dasar nelayan, membina kerjasama yang intens antar lembaga sektoral, serta pembuatan kebijakan yang efisien dalam pengentasan kemiskinan khususnya di wilayah pesisir.Kata Kunci : Kemiskinan, Nelayan, Pemerintah, Strategi Kolaborasi, Indonesia.